Juridical Review of Government Regulation 40 of 2019 Regarding the Marriage of Believers in Indonesia - Saputro, Dwi Yudha; Muchtar, Andhyka (CV. Rayyan Dwi Bharata, 2024)
Marriage registration for religious beliefs in Indonesia has been recognized by the state, whereas previously there was no recognition from the state and there was no legal certainty for adherents of this religious belief. The recognition of the religious beliefs that exist in Indonesia as beliefs and religions is good news for all believers in Indonesia, where the condition is that adherents of these beliefs have registered with the Ministry of Education, Culture, Research and Technology. This is as regulated in PP Number 40 of 2019 concerning Population Administration, where this regulation regulates all forms of administration and procedures for registering marriages for believers. This research uses a normative legal approach method. In this research, library data collection techniques (library research). The results of research on the Juridical Review of PP 40 of 2019 on the Marriages of Believers in Indonesia show that the registration of marriages for adherents of this religion is contained in Government Regulation Number 40 of 2019 concerning population administration, in this Government Regulation regulates marriage procedures for adherents of the faith who wish to those carrying out a marriage can register their marriage at the government's public service agency, namely at the Regency/City Population and Civil Registration Service where the prospective couple is domiciled. The legal obstacles that arise in registering marriages of believers in Indonesia make the implementation of PP Number 40 of 2019 still ineffective due to the lack of religious leaders who have a decree to marry prospective couples who want to get married, so difficulties will arise in the process of registering marriages at the Population Service Office. and Civil Registration if it is slow or impossible to issue a Letter of Blessing for a Faithful Couple who has entered into a Marriage.